Maternal and Fetal Outcome in Gestational Diabetes Mellitus - Noor, Sumia; Durwesh, Ayesha; Fazal, Safia; Riaz, Asma; Khan, Sundas (Indus Journal of Bioscience Research, 2025)
Background: Gestational diabetes mellitus is a frequent metabolic disorder of pregnancy, which is related to severe maternal and fetal complications. Despite the existence of documented worldwide data, inter-regional variations between populations, care access, and antenatal care policies require local investigations to clarify patterns of outcomes and to inform clinical decision-making. Objective: To determine the frequency of maternal and fetal outcome in patients with gestational diabetes mellitus. Study Design: Descriptive cross-sectional study. Duration and Place of Study: The study was conducted from April to October 2024 at the Department of Obstetrics and Gynecology, Ayub Teaching Hospital, Abbottabad. Methodology: A total of 139 pregnant women diagnosed with GDM after 20 weeks of gestation were enrolled. Maternal and neonatal outcomes including preeclampsia, polyhydramnios, low birth weight, respiratory distress, and hyperbilirubinemia were assessed. Demographic and clinical data were documented, and outcomes were stratified by age, BMI, parity, socioeconomic status, education, residence, and family history. Results: The mean maternal age was 30.60±6.03 years and BMI was 26.42±2.94 kg/m². The most frequent complications were preeclampsia (20.10%), low birth weight (13.70%), polyhydramnios (12.20%), respiratory distress (10.80%), and hyperbilirubinemia (9.40%). Significant associations were found between maternal age >30 years, BMI >25 kg/m², higher parity, and increased rates of complications. Conclusion: Gestational diabetes mellitus is associated with a high burden of maternal and fetal complications.